2016
DOI: 10.1142/s0192415x16500634
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects ofLiriope platyphyllain LPS-Stimulated Macrophages and Endotoxemic Mice

Abstract: In the present study, the anti-inflammatory and antisepticemic activities of a water extract of Liriope platyphylla (LP) were investigated. We first estimated the scavenging activity of DPPH and the hydroxyl radical and total phenolic contents of LP. Results indicated that LP, a rich source of phenolic compounds, showed a remarkable radical scavenging capacity. A MTT assay showed that LP treatment did not affect the toxicity against the RAW 264.7 macrophage cells, up to the concentration of 500[Formula: see te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Cells were cultured in DMEM supplemented with 10% of FBS, streptomycin (100 μg/ml), and penicillin (100 units/ml) incubated overnight at 37°C and 5% CO 2 . [ 12 ]…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cultured in DMEM supplemented with 10% of FBS, streptomycin (100 μg/ml), and penicillin (100 units/ml) incubated overnight at 37°C and 5% CO 2 . [ 12 ]…”
Section: Methodsmentioning
confidence: 99%
“…Liriope platyphylla is traditional medicine, which suggested a protective role of LPE in anti-obesity and anti-inflammatory effects. 111 Le TNH et al 112 showed that the treatment with Liriope platyphylla root ethanolic extract (LPE) reduced the protein expression of CD36 both in vivo and in vitro, leading to reduced fatty acid uptake.…”
Section: Natural Products That Affect the Occurrence And Development ...mentioning
confidence: 99%
“…The hot water extract from L. platyphylla tuber inhibits the production of inflammatory mediators such as nitric oxide (NO), interleukin-6 (IL-6), tumor necrosis factor (TNF) and prostaglandin (PG) E2 on RAW 264.7 macrophages cells treated by LPS (Kim et al, 2016). Therefore, in this study, antiencephalitic activity was measured for centrifugal supernatant and pellet according to methanol concentration to analyze functional materials in hot water and homogenized extracts.…”
Section: Methanol Fractionation After Hot Water Extract From L Platymentioning
confidence: 99%